2015
DOI: 10.1051/radiopro/2014036
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the need for a routine monitoring program in three Nuclear Medicine centers in Chile

Abstract: -The workers performing different activities with radionuclides in nuclear medicine centers are at potential risk of external exposure and internal contamination. The IAEA Safety Guide N• RS-G-1.2 proposed criteria for determining the need for a routine monitoring program to assess internal contamination. For this purpose, an Excel template containing the IAEA criteria was applied in three nuclear medicine centers in Chile. The results show that it is necessary to carry out a routine monitoring program for fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
3
0
3
Order By: Relevance
“…Astudillo et al . [ 21 ] also conducted a similar research in three nuclear medicine centers on the basis of IAEA criteria, and found it is necessary to carry out a routine monitoring program for five workers who handle 131 I and three workers who handle 99m Tc, where there were in total seven workers who handled 131 I and five workers who handled 99m Tc. Hence more than half of the workers investigated should be subjected to internal monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Astudillo et al . [ 21 ] also conducted a similar research in three nuclear medicine centers on the basis of IAEA criteria, and found it is necessary to carry out a routine monitoring program for five workers who handle 131 I and three workers who handle 99m Tc, where there were in total seven workers who handled 131 I and five workers who handled 99m Tc. Hence more than half of the workers investigated should be subjected to internal monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, considering that the decision factor assessment may overestimate the committed effective dose [ 21 ], internal monitoring work is needed to solve the problem of what dose from internal radiation the staff actually receive. Internal monitoring can be conducted in three ways: direct measurement of radionuclide in whole body or some organs, excreta or other biological samples analysis and air sampling analysis, respectively [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em outros países da América Latina e Caribe [16][17][18] , na América do Norte [19][20][21] , Europa [22][23][24] e Ásia 25,26 , a situação da monitoração interna em medicina nuclear é bastante semelhante à do Brasil. Em alguns países, assim como no Brasil, foram desenvolvidas metodologias de monitoração utilizando os recursos disponíveis nas próprias clínicas.…”
Section: Discussionunclassified
“…y 𝛽 ! , para el 22 Na y el 36 Cl, respectivamente que el electrón o positrón se expulsa puede ir desde la máxima permitida por la desintegración (si el neutrino no recibe energía), hasta el caso contrario en el que la energía cinética aportada al electrón o positrón es nula [6]. Por lo que, en estos dos tipos de desintegración el espectro energético de las partículas betas (electrones o positrones) es continuo.…”
Section: Decaimiento Radiactivounclassified